Dietary intake, physical activity and muscle strength among adolescents: the Malaysian Health and Adolescents Longitudinal Research Team (MyHeART) study - Ng, Ai Kah; Hairi, Noran Naqiah; Jalaludin, Muhammad Yazid; Majid, Hazreen Abdul (BMJ Publishing Group, 2019)
Objective To examine the role of dietary intake and physical activity in muscle strength among adolescents. Design Cross-sectional analysis. Setting The Malaysian Health and Adolescents Longitudinal Research Team (MyHeART) study. Participants Fifteen-year-old secondary school children who have given consent and who participated in the MyHeART study in 2014. Primary outcome measure Muscle strength was measured in relation to dietary intake (energy and macronutrients) and physical activity by using a hand grip dynamometer. Results Among the 1012 participants (395 male; 617 female), the hand grip strength of the males was higher than that of the females (27.08 kg vs 18.63 kg; p<0.001). Also, males were more active (2.43vs2.12; p<0.001) and consumed a higher amount of energy (2047 kcal vs 1738 kcal; p<0.001), carbohydrate (280.71 g vs 229.31 g; p<0.001) and protein (1.46 g/kg body weight (BW) vs 1.35 g/kg BW; p<0.168). After controlling for ethnicity, place of residency and body mass index, there was a positive relationship between hand grip strength and the intake of energy (r=0.14; p=0.006), carbohydrate (r=0.153; p=0.002) and fat (r=0.124; p=0.014) and the physical activity score (r=0.170; p=0.001) and a negative relationship between hand grip strength and the intake of protein (r=-0.134; p=0.008), for males. However, this was not observed among females. Conclusions Energy, carbohydrate and fat intakes and physical activity score were positively correlated with hand grip strength while protein intake was negatively correlated with hand grip strength in males but not in females. © Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.